Gynecology Fourth-Year Elective Rotation Curriculum - Petra Casey (Association of American Medical Colleges, 2008)
Abstract This resource describes a 4-week rotation for fourth-year medical students in a gynecology and related subspecialty clinic designed to deepen student knowledge of outpatient gynecologic care. Prerequisites include successful completion of the third-year OB/GYN clerkship and an interest in OB/GYN and women's health. Students see clinic patients with a faculty member or chief resident. The rotation also includes a didactic and skill portion for common gynecologic procedures, including biopsies, contraceptive management, endometrial sampling, and others. In addition, students complete two presentations on clinically related topics of interest, attend departmental conferences, and, if desired, begin a mentored research project in a field of interest. Evaluation of a student comprises written evaluations by all preceptors (30% of grade), assessment of the two presentations (20% of grade), completion of a procedural skills simulation (30% of grade), and a clinically based multiple-choice examination (20% of grade). Students also receive mid-rotation and end-of-rotation feedback sessions from the course director. This resource formalizes an effort to build on the basic OB/GYN clerkship knowledge and skills. It has been very well received by students. The rotation can be lengthened or shortened as needed.